Intracellular calcium levels as screening tool for nanoparticle toxicity. Issue 10 (14th May 2015) - Meindl, Claudia; Kueznik, Tatjana; Bösch, Martina; Roblegg, Eva; Fröhlich, Eleonore
Abstract: The use of engineered nano‐sized materials led to revolutionary developments in many industrial applications and in the medical field. These materials, however, also may cause cytotoxicity. In addition to size, surface properties and shape were identified as relevant parameters for cell damage. Cell damage may occur as disruption of membrane integrity, induction of apoptosis and by organelle damage. Generation of oxidative stress may serve as an indicator for cytotoxicity. Effects occurring upon short contact of particles with cells, for instance in the systemic blood circulation, could be identified according to increases of intracellular [Ca 2+ ] levels, which are caused by variety of toxic stimuli. Negatively charged, neutral and positively charged polystyrene particles of different sizes were used to study the role of size and surface properties on viability, membrane disruption, apoptosis, lysosome function, intracellular [Ca 2+ ] levels and generation of oxidative stress. Silica particles served to test this hypothesis. Twenty nm polystyrene particles as well as 12 nm and 40 nm silica particles caused membrane damage and apoptosis with no preference of the surface charge. Only 20 nm plain and amine functionalized polystyrene particles cause oxidative stress and only the plain particles lysosomal damage. A potential role of surface charge was identified for 200 nm polystyrene particles, where only the amidine particles caused lysosomal damage. Increases in intracellular [Ca 2+ ] levels and cytotoxicity after 24 h was often linked but determination of intracellular [Ca 2+ ] levels could serve to characterize further the type of membrane damage. © 2015 The Authors. Journal of Applied Toxicology Published by John Wiley & Sons Ltd. Abstract : Nano‐sized materials may cause cytotoxicity. Negatively charged, neutral and positively charged polystyrene particles of different sizes and silica nanoparticles were used to study the role of size and surface properties on viability, membrane disruption, apoptosis, lysosome function, intracellular [Ca 2+ ] levels and generation of oxidative stress. Small polystyrene particles and silica particles caused membrane damage and apoptosis with no preference of the surface charge. Increases in intracellular [Ca 2+ ] levels could be used as a screening tool for cytotoxicity.